Hydrodynamic and suspended sediment transport controls on river mouth morphology. Issue 1 (14th January 2014) - Falcini, F.; Piliouras, A.; Garra, R.; Guerin, A.; Jerolmack, D. J.; Rowland, J.; Paola, C.
Abstract [1] River mouths building into standing bodies of water have strikingly varied growth habits. This presents a compelling pattern formation problem that is also of great practical relevance for subsurface prediction and managing coastal wetlands. Here we present a generalized 2.5‐dimensional potential vorticity (PV) theory that explains sedimentation patterns of a sediment‐laden stationary jet by coupling an understanding of vorticity with suspended sediment concentration fields. We explore the physical meaning of this new sediment‐PV definition, and its impact on outflow depositional patterns, by analyzing data from a shallow wall‐bounded plane jet experiment and by discussing new theoretical insights. A key result is that lateral advection and diffusion of suspended sediment are directly proportional to jet vorticity, a feature that reveals the mechanistic process that forms elongated channels by focused levee deposition. The new PV theory constitutes a more generalized mathematical framework that expands the Rouse theory for the equilibrium of suspended sediment.